Psychological resilience in childhood: Critical analysis of the concept - Giedraitytė, Marija; Bieliauskaitė, Rasa (Psichologija, 2006)
The primary purpose of the article is to critically analyze the concept of resilience integrating the most recent research findings and showing implications for future studies. The construct of resilience was proposed in order to explain why some children adapt well despite adversity (as early studies on the negative impact of risk factors had shown). This brought about a higher attention to protective factors and mechanisms. During this period developmental psychopathology emerged as a distinct field of study, which provided theoretical principles for the analysis of normal and abnormal development. The research on resilience was later extended to adult populations. Resilience is a process influenced by many factors, not a personal feature. It should accordingly be used with precaution. The Lithuanian term “atsparumas” has the disadvantage of suggesting that it is a trait possessed by the child. Possible alternatives could be “atsparavimas” or “rezilencija”. Today most scholars accept Luthar, Cicchetti and Becker’s (2000a) definition of resilience, which is broad enough to allow for various operationalizations of the various aspects of resilience and at the same time narrows conveniently the field of research. They define resilience as a dynamic process of positive adaptation in the context of significant adversity. The following aspects are particularly important: Risk: its evaluation should take into account the different ways in which the same risk can be experienced, the possible genetic mediation of familial variables, and children’s active participation in determining risk effects. Positive developmental outcomes: how they are defined partly depends on the researcher’s personal choices, but superior functioning should not be expected. Process of resilience: protective factors must be clearly defined and separated from protective processes. Current research is revealing a number of characteristics of the resilience construct with important implications for both research and practice. Several studies have confirmed that resilience is a multidimensional construct so that it is necessary to take into due consideration the different areas of adaptation. It is also clear that resilience changes over time (as should be expected), but on the other hand, its relative stability has also been defended. Finally, it remains an open question whether resilient adaptation differs from that found in normal circumstances. The actual data are contradictory and further research in this area is badly needed. As far as the theoretical framework of the research on resilience is concerned, it is based mainly on the principles of developmental psychopathology. The theoretical perspective of levels of resilient processes and that of human-context interaction are also relevant. The dynamic systems theory is a promising tool for future research in this area. It would also be possible to make further assumptions about the positive character of human nature or about inherent adaptive systems in order to look for deeper sources of resilience. The second source of resilience could be seen in the role played by human relationship, which is also very important. We showed several problematic aspects of the concept of resilience. While growing empirical data allow answering some questions, there still is a lot of room for research. Two challenging tasks remain for the future: on the one hand, the application of our theoretical knowledge on resilience to real-life situations, on the other hand, the development of theories explaining the basic processes of adaptation under adverse circumstances.